Conservação genética e reposição de estoques nativos na bacia do rio Sapucaí-Mirim (SP) - Mendonça, Bruna Bueno [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The Sapucaí-Mirim River, tributary of Alto Paraná basin presents great diversity of Neotropical fishes in terms of richness of species. Nevertheless, the region which encompasses the Paraná and Alto Paraná basins presents a great anthropic interference especially due to the construction of hydroelectric plants, these constructions can be classified as to its capacity to generate energy, in Hydroelectric plants and Small Hydroelectric Plants (SHP). The SHP are considered by several authors as one of the alternatives with less interference, due to its small size, this kind of hydroelectric are constructed to feed the energetic demand of small urban and rural centers. However, the constructions of SHPs together with hydroelectric plants constructions causes an even bigger fragmentation in the aquatic environments , which results in the interruption of rivers flow, this event has been shown as very harmful to fishes species specially the migratory species. Once a year these species move upstream to feed and reproduce, due to dams constructions migratory fishes species have difficulties to complete their life cycle. Several studies indicates the dams as a principal factor in the reduction of migratory species population , warning to necessity of conservationist actions, aiming to maintain the fisheries stocks that represent a fisheries and ecological importance in the aquatic environments. Many actions are employed aiming to minimize the reduction of migratory species population, however, in Brazil these actions are performed without scientific support, occurring in a wrongful manner, specially the restocking, where the fishes are released into the wild without any prior biological and genetic knowledge. Mitigation practices performed without scientific support may endanger the wild stocking. The development of genetics technologies has been proven of extremely importance to assist in the ecology and conservationist biology, through ...

O rio Sapucaí-Mirim, tributário da bacia do Alto Paraná apresenta grande diversidade de peixes neotropicais, em termo de riqueza de espécies. Paradoxalmente, a região que compreende a bacia do rio Paraná e alto Paraná apresenta uma grande interferência antrópica devido principalmente a construção de centrais hidrelétricas. Centrais hidrelétricas podem ser classificadas em Usinas Hidrelétricas (UHE) e Pequenas Centrais Hidrelétricas (PCH), de acordo com a capacidade de gerar energia. As PCHs são colocadas por vários autores como uma das alternativas de menor interferência, por apresentarem um tamanho reduzido, sendo construídas para suprir a demanda energética de pequenos centros urbanos e rurais. No entanto, a construção de diversas PCHs somada a construções de UHE causam uma fragmentação ainda maior nos ambientes aquáticos, ocasionando a interrupção do fluxo dos rios, este evento tem se mostrado prejudicial para várias espécies de peixes, principalmente as espécies migradoras. Estas espécies têm a necessidade de movimentar-se rio acima para fins tróficos e reprodutivos uma vez ao ano, com a construção de barramentos estas encontram dificuldades para completar seu ciclo de vida. Diversos estudos apontam esse bloqueio como principal fator na redução populacional destas espécies, alertando para necessidade de ações conservacionistas, a fim de manter os estoques pesqueiros que além de apresentarem importância ecológica nos ambientes aquáticos são de grande importância na pesca comercial e de subsistência. Há diversas ações tomadas para mitigar a redução populacional destas espécies, no entanto, no Brasil, estas ações são realizadas sem informações científicas, ocorrendo de forma equivocada, especialmente em práticas de repovoamento, onde alevinos são liberados na natureza sem nenhum conhecimento prévio biológico e genético. Práticas mitigadoras realizadas sem respaldo ....
Keywords: Peixe - População; Diversidade genética; Biodiversidade - Conservação; Usinas hidrelétricas; Biodiversity conservation